100 Great Books: Masterpieces of All Time.
Here is the ideal guide for all those who wish to read more of the world\'s great books, but find themselves bewildered by the very richness of the choices open to them. The editor has selected one hundred of the greatest books of all time, discussing them in a penetrating yet highly readable way